RANCANG BANGUN RUANG PINTAR MINIMALIS TENAGA SURYA DENGAN SISTEM KONTROL BERBASIS ARDUINO - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
This study aims to design a concept of Smart Room System with a source of electricity derived from the Solar Cell System in a home which can facilitate human activities while in the house such as turning on and off the lights, open and close the door of the house. Smart Room System is a technology that allows homeowners to control the entire contents of the house in one hand, can be a smartphone or other gadgets. In improving security and comfort, this system is controlled by Arduino microcontroller. Arduino is connected to a computer via USB, programmed using C language via Arduino IDE by uploading compiled code to Arduino board. Arduino microcontrollers can be utilized as a home light controller, automatic door control and feature controller of other electronic devices. Associated with the many electronic features used in the Smart Room System, the source of electricity used is from a solar power plant that is known that solar or solar is one source of renewable energy is much cheaper, environmentally friendly and more efficient because it minimizes the use of sources electricity PLN 220 V.